Femtosecond inscription of semi-aperiodic multi-notch fiber Bragg gratings using a phase mask - Goebel, T. A.; Heusinger, M.; Kraemer, R. G.; Matzdorf, C.; Imogore, T. O.; Richter, D.; Zeitner, U. D.; Nolte, Stefan (Optics Express, 2020)
We present an innovative concept of a semi-aperiodic phase mask design that enables the realization of multi-notch fiber Bragg gratings (FBG). This design utilizes the overlap and interference of near-infrared ultrashort laser pulses diffracted by short sequenced phase mask sections, which not only allows for a highly stable and reproducible inscription of a large number of wavelength filters but also paves the way towards full aperiodic phase masks. The semi-aperiodic FBG inscribed by this phase mask enables versatile notch filters showing multiple non-equidistant resonances. Those filters target applications, for instance in ground-based telescopes, where a large number of hydroxyl emission lines emitted in the upper atmosphere at near-infrared wavelengths restrict the observation of faint extraterrestrial objects.
CRIS-Team Scopus Importer:2023-04-20